Zur Wüstungs- und Kulturlandschaftsforschung - Jäger, Helmut (ERDKUNDE, 1954)
This paper communicates results of investigations which were carried out by the author recent years in the field of settlement desertion and cultural landscape study. The paper deals particularly with „Wüstungsfluren“ , deserted fields, according to their type and layout, and their significance for geographical and historical research. The stages reached in various countries in research on deserted fields is reviewed in a short section. The question of the origin of „Hochäcker“ (ridges and furrows) and „Hochrainen“ (cultivation terraces, lynchets) is answered. Ridge and furrow are the result of a special type of tillage, primarily conditioned by humidity and type of soil; this method of tillage was particularly advantageous when a plough with unre- versable mouldboard was used. Certain circumstances indicate that ridge and furrow widely distributed over North Germany and Jutland even before 500 A.D. As regards the origin of lynchets, the author agrees with O. G. S. Crawford and Kuhn; as a type of tillage, lynchets are older than ridge and furrow. To the geographer the dating of deserted fields is not an end in itself, but by using them as guiding fossils, a means to a genetic approach to the study of the cultural landscape. Both Medieval ridges and furrows as well as lynchets under a forest cover are widely found in Middle Europe. The investigation of such deserted fields showed that in the Middle Ages there were in various German regions certain place and field types which could no longer be found in the same areas during the modern period. The rural cultural landscape has in many cases changed to a -much greater degree than was formerly believed. The study of but temporarily deserted settlements proved in this respect most rewarding. The author has begun to try and establish regions and periods of a uniform type of landscape development. The desertion period started in parts of Hesse and adjoining regions at the beginning of the 14th century and lasted until the middle of the 15th century. This dating takes much weight off the theory that there are connexions between climatic changes and the desertion of settlements, at least as far as this region is concerned. The concept of the „Altlandschaft“ (historic landscape) is put forward anew for discussion. Very early and continuously settled regions may, if they suffered a desertion period, possess very youthful features in their landscape, whereas in contrast, late settled regions, where no desertion of settlements occured, may exhibit settlements, places and fields, of a much older type. Finally it is stated, that when dealing with the late Medieval desertion period, the changes in the political and sociological structure should be considered more than has been done hitherto.